The Effect Of Management Control System, Work Discipline, Work Motivation, And The Application Of Good Corporate Governance Principles On Employee Performance - Thoha, Muhammad Nuur Farid; Febriantoro, Krisna Adji (Sean Institute, 2025)
This study aims to determine the effect of Management Control System, Work Discipline, Work Motivation and Implementation of Good Corporate Governance Principles on Employee Performance at PT. Asuransi Perisai Listrik Nasional, Jakarta head office. The population of this study were 215 employees of PT Asuransi Perisai Listrik Nasional (Jakarta headquarters). Sampling was carried out using Non Probability Sampling Technique with Purposive Sampling sampling method. The sample determination was calculated using the Slovin formula with the results of 140 respondents. Data collected through a questionnaire with a Likert scale with 4 scales, processed with Microsoft Excel 2019 and data analysis using SPSS version 22. The research method used is multiple linear regression. The results of the study prove that the Management Control System has no effect on Employee Performance, Work Discipline affects Employee Performance, Work Motivation affects Employee Performance and the Principles of Good Corporate Governance affect Employee Performance